Assessment of community noise problem in greater Beirut area, Lebanon - Korfali, Samira Ibrahim (2003)
Over the last two decades, urban noise has been increasingrapidly, primarily in urban areas, due to population growthand the increase of certain noise sources. The main objectiveof this paper is to assess the sources and possible impactsof the community noise problems in Lebanese urban areas,particularly the Greater Beirut Area. The causes and effectsof community noise pollution are briefly presented. Soundpressure levels that were measured to define existing noiseexposure levels in various locations in the Greater BeirutArea are also presented. The attitudes toward noise pollutionand perceived annoyance impact on a sample of 1,038 exposedresidents are described. The association between measurednoise levels and sources, as well as annoyance, is examinedusing correlation analysis and linear and multiple linearregressions. A set of recommendations is presented to reducecommunity noise problem in Greater Beirut Area.